Transcatheter mitral valve replacement in native mitral valve with severe mitral annular calcification: Skirting the Sapien 3 to reduce the risk of paravalvular leaks - Pozzoli, Alberto; Torre, Tiziano; Pedrazzini, Giovanni; Demertzis, Stefanos; Ferrari, Enrico (Frontiers in Cardiovascular Medicine, 2022)
Background Mitral annular calcification (MAC) may represent a significant challenge for heart surgeons with an extremely high perioperative risk during mitral valve (MV) surgery. The risk is further increased when patients fail to be eligible for any percutaneous treatment, particularly because circumferential calcifications involving the anterior leaflet suggest a critical obstruction of the left ventricular outflow tract (LVOT). Objectives The objective of this study was to evaluate residual mitral regurgitation (MR) after surgical mitral valve replacement using a Sapien 3 Ultra (Edwards Lifesciences, CA, USA) transcatheter aortic valve implantation (TAVI) prosthesis, reinforced with a pericardial skirt, in high-risk selected patients with severe MAC. Methods Since 2020, five high-risk patients (mean age 70 years; 63–76; four women) with severe mitral disease in the context of severe MAC (computed tomography-based mean MAC Score 8.2 ± 1.1) were operated on after we adopted this novel technique. The operations were performed under general anesthesia, using a transapical TAVI delivery system to position the Sapien 3 in the mitral position under direct vision. To reinforce and avoid paravalvular leakages, a pericardial skirt was previously sewn around the prosthesis, securing it to the annulus and perivalvular atrial surface. Results Sapien 3 Ultra implantation was successful without residual MR in all five patients (mild paravalvular leak in one case). Four patients had a 29-mm valve implanted, while one had a 26-mm valve implanted. Predilatation of the native annulus was never performed. Perfusion and clamping times were 134 ± 53 mins and 108 ± 43 mins, respectively. The presence of the pericardial skirt reduced the risk of leakage between the prosthesis and the rigid calcium surface, with final mean and maximal gradients of the TAVI prosthesis of 4.1 and 10.8 mmHg, respectively. There were no left ventricular outflow tract obstructions (mean LVOT gradient of 8 ± 1 mmHg). All patients were discharged, and neither mortality nor prosthetic dysfunction, nor residual mitral regurgitation was recorded. During follow-up, the last patient treated (MAC Score 10, severe calcification of the mitro-aortic junction) returned to our attention with a significant recurrent jet originating from the anterolateral commissure, currently medically treated, given the prohibitive redo risk. Conclusion Direct open surgical implantation of the Sapien 3 valve can be safely done in patients with severe MAC in dedicated centers. Reinforcing the TAVI prosthesis by sewing a pericardial skirt led to satisfactory perioperative and early postoperative results, reducing paravalvular leakages. Complex anatomies have a CERTAIN risk of recurrence.